Антиєврейський погромний рух в Україні у 1919 році - Лазарович, М. В.; Лазарович, М. В.; Lazarovich, M. (My University, 2012)
Intensity of development of the antiJewish pogrom movement in Ukraine during 1919 is tracked. Are certain the basic forces involved in its fulﬁ lment, and district of the largest displays. It is found out consequences of pogrom actions.
Лазарович М. В. Антиєврейський погромний рух в Україні у 1919 році / М. В. Лазарович // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 367-377.
Keywords: антиєврейський погромний рух в Україні 1919 р.; місцевості проявів антиєврейського погромного руху в Україні; здійснення антиєврейських погромів в Україні; наслідки погромницьких дій; антиеврейское погромное движение в Украине в 1919 г.; места проявлений антиеврейского погромного движения в Украине; осуществление антиеврейских погромов в Украине; последствия погромов; anti-Jewish pogrom movement in Ukraine in 1919; manifestations of anti-Jewish pogrom place movement in Ukraine; implementation of anti-Jewish pogroms in Ukraine; the effects of riots